Unix Survival Guide. Issue 1 (3rd September 2015) - Stein, Lincoln D.
Abstract: Most bioinformatics software has been designed to run on Linux and other Unix‐like systems. Unix is different from most desktop operating systems because it makes extensive use of a text‐only command‐line interface. It can be a challenge to become familiar with the command line, but once a person becomes used to it, there are significant rewards, such as the ability to string a commonly used series of commands together with a script. This appendix will get you started with the command line and other Unix essentials. © 2015 by John Wiley & Sons, Inc.